Occurrence of Equine West Nile Virus Among Horses in Qatar :A Preliminary Investigation - M. Haroun; A. M. Siddiq; E. A. Farag; Elyes Dlissi; A. M. El Hussein; H. O. Mohammed (European Scientific Journal, ESJ, 2017)
West Nile Virus (WNV) is an emerging threat to public health authorities around the globe. WNV is maintained in ecosystems primarily in enzootic cycles involving mosquito vector and avian hosts, with epizootic spread to mammals including horses and humans. Outbreaks of WNV disease in mammals have been associated with significant losses. The factors that play roles in the evaluation of these outbreaks are not fully known and the disease has not been reported in Qatar. We carried out a study to determine the prevalence of exposure to WNV in the State of Qatar and identify the factors that are likely to associate with seroconverion.